Analisis kualitas air tanah dan air permukaan disekitar tpa km 14 kota palangka raya: Analisis kualitas air tanah dan air permukaan disekitar tpa km 14 kota - Emi Asokawati; Achmad Imam; Sari Marlina (Fakultas Teknik Universitas Pasifik Morotai, 2022)
The Palangkaraya City Final Processing Site (TPA) produces quite a lot of waste and creates a new problem in the form of leachate runoff. Leachate water can seep into groundwater and swamps, reducing the quality of surface water and groundwater around the landfill. The leachate contains decaying organic materials and heavy metals such as iron (Fe), cadmium (Cd), mercury (Hg) and lead (Pb). These metals are known to affect the health conditions of humans and other living things. The research method used in this study is qualitative exploratory research results on the quality of surface and soil water related to chemical parameters, physics such as indicators obtained pH (6.97-8.4), Pb (0.059 Mg / L - 0.0503 Mg / L ) Cd (0.003 Mg / L -0.0.0026 Mg / L ), Fe ( 0.056 Mg / L - 0.0310 Mg / L ) and ° C (30-31) these indicate the quality of water around the landfill based on regulation No. According to SNI 6989.84 2019, surface water and ground water around the TPA are not recommended for consumption because they have an impact on human health.